Keputusan Pembelian Ditinjau Dari Persepsi Harga, Kualitas Pelayanan, Dan Kualitas Produk Pada PT Mitra Anda Abadi Klaten - Adzra Belvana Bassamah; Sarsono; Sudarwati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to determine the perception of price, service, and product quality impacting purchasing decisions at PT Mitra Anda Abadi Klaten, in Klaten, Central Java. Materials and methods. Using quantitative descriptive methods and non-probability purposive sampling. With a 95% confidence level and a 10% margin of error, the Sugiyono formula was used to determine a sample of 100 respondents. Prior to hypothesis testing, the instruments were checked for validity and reliability, and the regression model was tested for normality, multicollinearity, and heteroscedasticity. Data were analyzed using SPSS using multiple linear regression. Results. Price perception does not have a positive and significant effect on purchasing decisions (t-count = 1.881 < t-table = 2.040; sig. = 0.063); service quality has a positive and significant effect on purchasing decisions (t-count = 3.567 > t-table = 1.985; sig. = 0.001); and product quality does not have a positive and significant effect on purchasing decisions (t-count = 1.967 < t-table = 1.985; sig. = 0.052). The adjusted R-square value of 0.424 indicates that the three variables studied explain 42.4% of the variance, while the remaining 57.6% is attributable to variables outside this study. Conclusions. Service quality is the primary factor influencing the three variables. Perceptions of price and product quality do not significantly influence customers' purchasing decisions, but both together significantly influence their decisions.